If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = k + 54 Reorder the terms: -18 = 54 + k Solving -18 = 54 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. -18 + -1k = 54 + k + -1k Combine like terms: k + -1k = 0 -18 + -1k = 54 + 0 -18 + -1k = 54 Add '18' to each side of the equation. -18 + 18 + -1k = 54 + 18 Combine like terms: -18 + 18 = 0 0 + -1k = 54 + 18 -1k = 54 + 18 Combine like terms: 54 + 18 = 72 -1k = 72 Divide each side by '-1'. k = -72 Simplifying k = -72
| 0=10w-10 | | 4-(-5+x)=-9 | | 3(2z-4)-4z=-1.5(20z+10) | | 4=5x+6x+4 | | -3q^2+6q-3=0 | | -56+n^2+n= | | 8(x-3)=48 | | 7=38-3 | | 17-2v=41 | | 12-2(n-3)=-2 | | -3(2m-1)+4m=-3m+11 | | -2s^2+5s-2=0 | | 3(x-2)=6x-12 | | (7x)=(4x^9) | | 3x/3=9 | | 3h-5(h+3)-h=3-2(3h+4) | | 3h-5(h+3)-h=3-2(3h+4) | | 5=13n-21 | | 2-2(2x+7)+7x=2x+3(4-9x) | | -3(2z-8)+102=16 | | -2=4r^2+8r | | -g^2+3g+8=0 | | 3t-5t+20=-8 | | 4b-1=-13 | | -9m^2-9m+5=0 | | 5h^2-4h-9=0 | | 2y+-3y=7 | | f(x)=35p^2-18p-5 | | 16x+7=x+22 | | 22=5-3x | | 2r^2-32r=2 | | 5-3x=22 |